The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0cc00106f
|View full text |Cite
|
Sign up to set email alerts
|

Gold and hypervalent iodine(iii): liaisons over a decade for electrophilic functional group transfer reactions

Abstract: Building on mechanistic perspective, the review intends to demonstrate how the uniqueness of Au-catalysts has realized a myriad of electrophilic functional group transfer reactions with the use of hypervalent iodine(iii) reagents over the last decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 125 publications
0
53
0
Order By: Relevance
“…448 Early in 2020 Patil and co-workers have critically reviewed the gold-EBX catalyst system, with particular emphasis on the various mechanistic alternatives, and this chemistry will therefore not be discussed here in detail. 449 The most active catalyst seems to be "ligand-free" AuCl. Given that AuCl is a coordination polymer that consists of chains held together by a network of aurophilic interactions, the precise nature of the catalyst under the reaction conditions must remain a matter of speculation.…”
Section: Scheme 105 Oxidative Aryl-aryl Coupling Of Two Different Nucleophilesmentioning
confidence: 99%
“…448 Early in 2020 Patil and co-workers have critically reviewed the gold-EBX catalyst system, with particular emphasis on the various mechanistic alternatives, and this chemistry will therefore not be discussed here in detail. 449 The most active catalyst seems to be "ligand-free" AuCl. Given that AuCl is a coordination polymer that consists of chains held together by a network of aurophilic interactions, the precise nature of the catalyst under the reaction conditions must remain a matter of speculation.…”
Section: Scheme 105 Oxidative Aryl-aryl Coupling Of Two Different Nucleophilesmentioning
confidence: 99%
“…Nonetheless, the catalytic version of this transformation is still underdeveloped [11,[24][25][26]. Alternatively, Au(I) cross-coupling reactions have remained a challenge due to the reluctance of this metal to oxidize to Au(III), although this difficulty has been overcome through the use of co-oxidants [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…[27] Bipy-like ligands (e.g.,p hen) have received attention for their role in enabling Au I /Au III catalysis with hypervalent iodine(III) reagents. [28] Importantly,the results described here are distinct;for example,Hashmi and co-workers showed that the rate of oxidative addition of alkynyl À iodine(III) reagents to [(phen)AuPR 3 ]NTf 2 complexes does not have alinear relationship with the electronics of substituted phen ligands. [29] Instead, as trong linear correlation to the electronics of the PR 3 ligand was observed, with more weakly donating variants being most efficient (1 = 3.75).…”
Section: Methodsmentioning
confidence: 72%